2022
DOI: 10.3390/molecules27031008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermentation Beetroot Juice Process on the Physico-Chemical Properties of Spray Dried Powder

Abstract: Picking vegetables is, along with salting and drying, one of the oldest ways to preserve food in the world. This is the process of decomposition of simple sugars into lactic acid with the participation of lactic bacteria. The aim of the study was to obtain powders from fermented red beet juice with the highest possible amount of lactic acid bacteria (LAB) and active ingredients. For the analysis, juices were squeezed from the vegetables and two types of fermentation were used: a spontaneous fermentation and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
0
15
1
Order By: Relevance
“…In our previous research on the fermentation of red beetroot, we observed a decrease in both pigment contents [16,35,39]. Interestingly, the yellow pigments showed higher stability at a lower pH.…”
Section: Pigment Contentmentioning
confidence: 67%
See 3 more Smart Citations
“…In our previous research on the fermentation of red beetroot, we observed a decrease in both pigment contents [16,35,39]. Interestingly, the yellow pigments showed higher stability at a lower pH.…”
Section: Pigment Contentmentioning
confidence: 67%
“…Fermented foods are now consumed almost all over the world, and the variety of raw materials fermented depends on the region. Some of the best-known vegetables used for fermentation are cabbage, carrots, beetroots, cucumbers, onions, radishes, garlic, peppers, and olives [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because it contains microorganisms that break down organic debris, encourage development, and act as a biological controller, Biomol solution is suitable for use as an organic pesticide [3]. Several researchers, including (Sasmita et al, 2014) [4], have conducted biomol research, with the conclusion that administering local microorganisms (MOL) from the fruit promotes asexual growth in sweet potato plants. According to the findings of (Rahmah et al, 2014) [5], liquid organic fertilizers of varied concentrations had an effect on corn development.…”
Section: Introductionmentioning
confidence: 99%